Mechanochemical Synthesis as a Greener Way to Produce Iron‐based Oxygen Reduction Catalysts. Issue 22 (12th September 2021) - Gernhard, M.; Rautenberg, M.; Hörner, G.; Weber, B.; Emmerling, F.; Roth, C.
Abstract: Iron‐based catalysts have been reported manifold and studied as platinum group metal (PGM) free alternatives for the catalysis of the oxygen reduction reaction (ORR). However, their sustainable preparation by greener synthesis approaches is usually not discussed. In this work, we propose a new method for the sustainable preparation of such catalysts by using a mechanochemical approach, with no solvents and non‐toxic chemicals. The materials obtained from low temperature carbonization (700 °C) exhibit considerable and stable catalytic performance for ORR in alkaline medium. A catalyst obtained from iron hydroxide, tryptophan, dicyandiamide, and ammonium nitrate shows the best electrocatalytic performance with an overpotential of 921 mV vs. RHE at 0.1 mA/cm 2 and an electron transfer number of 3.4. Abstract :